2019
DOI: 10.21307/jofnem-2019-011
|View full text |Cite
|
Sign up to set email alerts
|

Agricultural intensification and urbanization negatively impact soil nematode richness and abundance: a meta-analysis

Abstract: Human activity has extensively transformed the land surface by agricultural intensification and urbanization. In soil, nematodes are the most abundant invertebrates. The effect of human interventions was assessed on overall richness, overall abundance, richness and abundance of nematodes of each trophic group and colonizerpersister (c-p) guild by comparing urban, agriculture and disturbed grassland (DGL) with natural grassland (NGL) and forest ecosystems. Meta-analyses were conducted to generate quantitative s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 44 publications
(72 reference statements)
1
17
0
Order By: Relevance
“…There have been several reports of taxonomic analyses of nematodes in forest [ 33 , 58 , 60 71 ] and agricultural field [ 11 , 13 , 15 17 , 19 22 , 30 , 72 ] soils. Studies on forest soils have shown that bacteria, plant, and fungus feeders occupy significant fractions of the nematode communities despite varied proportions by the sampling sites, periods, and environmental status of forests [ 33 , 62 , 68 , 70 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There have been several reports of taxonomic analyses of nematodes in forest [ 33 , 58 , 60 71 ] and agricultural field [ 11 , 13 , 15 17 , 19 22 , 30 , 72 ] soils. Studies on forest soils have shown that bacteria, plant, and fungus feeders occupy significant fractions of the nematode communities despite varied proportions by the sampling sites, periods, and environmental status of forests [ 33 , 62 , 68 , 70 ].…”
Section: Discussionmentioning
confidence: 99%
“…Nematode communities in agricultural fields have also been reported to contain mainly bacteria, fungus, and plant feeders, with minor groups of omnivores and predators [ 11 , 13 , 15 17 , 19 22 , 30 , 72 ]. However, the proportions of feeding groups in agricultural soils can be modified by tillage [ 15 , 20 , 21 ], fertilizers and compost treatments [ 13 , 15 17 , 19 , 20 , 22 ], or crop cultivation [ 16 , 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…These observations clearly indicate different environmental and biological conditions of copse soils from those of the field and flower bed soils. Pothula and colleagues have examined the impact of agricultural intensification and urbanization on soil nematode communities using 111 published articles and examined the richness and abundance of 5 trophic groups in 5 different environmental soils including forest [ 50 ], indicating that the order of abundance was herbivores (plant feeders) > bacterivores > fungivores and omnivores > predators despite high variation. So far, several taxonomic studies on soil nematode communities in forest soils have been known and were performed using morphogenic and sequence-based approaches over the world (Brazil [ 51 ], Canada [ 52 ], China [ 53 – 56 ], Germany [ 57 ], Japan [ 58 , 59 ], Slovakia [ 60 ], Sweden [ 61 ], USA [ 62 ]).…”
Section: Discussionmentioning
confidence: 99%
“…Although there is variability in the results regarding specific indicators of biological soil quality, recent meta-analyses have observed overall negative effects of agricultural management on the nematode community (Pothula et al 2019;Liu et al 2016) in line with the decrease in the nematode Structure index and the increase in the nematode I CS , reported in Chapter 4. The examples of literature presented above are a great start in understanding the effects of specific management decisions on biological soil quality, but it is necessary that these changes are adopted by farmers, which touches upon subjects discussed before and in the discussion of Chapter 5: providing incentives that make the adoption of sustainable practices less risky to farmers as well as tools that provide insight into management decisions not just to maximise primary productivity, but to do so sustainably.…”
Section: Arable Farming and Biological Soil Qualitymentioning
confidence: 93%
“…The multi-criteria decision models used to assess primary productivity (PP), nutrient cycling (NC) and biodiversity and habitat provision (B-HP) each had a different requirement in terms of input variables. If we assumed al sites to have the same value, we have underlined it.Soil biota are indispensable for the delivery of soil functions, but agricultural management has been shown to cause harm to soil biodiversity(de Graaff et al 2019;Emmerson et al 2016;Geiger et al 2010;Pothula et al 2019). This has been highlighted…”
mentioning
confidence: 99%